The Moral Significance of Religious Affections: A Reformed Perspective on Emotions and Moral Formation - Cochran, Elizabeth Agnew (Studies in Christian ethics, 2015)
Drawing on the work of Jonathan Edwards, this essay explores two dimensions of Reformed thought central to considering the emotions’ moral significance. First, Reformed theology’s singular understanding of virtue and holiness as love to God and neighbor gives rise to a distinctive account of the emotions’ place in the moral life. Certain emotions are to be embraced insofar as they have the capacity to be sanctified and thereby made compatible with growth in love to God. Second, Reformed theology historically links the emotions with the will, which is subject to moral necessity. Contemporary Reformed reflection on the emotions must therefore grapple with questions about moral agency and accountability that arise from this account of necessity.